PERSEPSI MASYARAKAT TERHADAP ASOSIASI MEREK (BRAND ASSOCIATION) KOMUNITAS DATA SCIENCE INDONESIA MELALUI KONTEN MEDIA SOSIAL INSTAGRAM - Aldy Nur Febrian; Djoko Murdowo; Andreas Rio Adriyanto (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
Digitalization and the internet have changed how people communicate and share information, including through Instagram. A community named Data Science Indonesia (DSI) aspires to become a medium for data literacy and knowledge related to data technology, especially in the data scientist profession. From 2021 to 2022, only 30 or around 11% of the content on Instagram was about data literacy or data technology education. The other 142 or 52.4% of the content is posters for online/ offline activities such as seminars and competitions in data. It is necessary to know that DSI's ideals align with what the community associates on Instagram. This study aims to determine public/ audience (followers) perceptions of DSI brand associations on Instagram. This mixed methods research uses a descriptive qualitative approach with observational data sources and questionnaires. Data analysis was done using the word cloud technique by grouping the keywords most frequently mentioned in the survey. The results of this study indicate that DSI's brand association on Instagram is partially in line with the expected community goals. Instagram becomes a representation/ face of a brand that can create perceptions and associations on certain things that must be aligned with the expected goals. Keywords: brand association, data science, instagram, perceptions, social media